2014
DOI: 10.14202/vetworld.2014.842-847
|View full text |Cite
|
Sign up to set email alerts
|

Age and lactation specific disposal pattern in Sahiwal cattle and influence of various genetic and non-genetic factors

Abstract: Premature disposal of female calves before reaching milch herd and undesirable disposal of lactating cows are the major constraints in achieving larger herd size. During the early lactations, younger cows are supposed to give higher milk yield and undesirable disposal of early calvers, thereby, greatly hampers profitability of a dairy farm. Knowledge of the incidence of disposal along with reasons in various age groups and at various parities is essential to identify which age group or parity is more vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 9 publications
11
2
0
Order By: Relevance
“…Abnormal birth: The overall incidence of abnormal birth in Sahiwal was 6.21% among the 1,885 calving (Table 1). Similar findings were reported by Upadhyay et al (2014) and Singh et al (2011) for Sahiwal cattle. Lower estimates than the present finding were reported by Shahi and Kumar (2006), Banik and Naskar (2006), Abbas (2005), Rawal and Tomar (1996) for Sahiwal, and Lathwal et al (1993) for Red Sindhi while higher estimates were observed by Upadhyay et al (2017) for Karan Fries; Goshu and Singh (2013) for HF cattle; Shahi and Kumar (2006) for J × SW cross and Atrey et al (2005) for Frieswal.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Abnormal birth: The overall incidence of abnormal birth in Sahiwal was 6.21% among the 1,885 calving (Table 1). Similar findings were reported by Upadhyay et al (2014) and Singh et al (2011) for Sahiwal cattle. Lower estimates than the present finding were reported by Shahi and Kumar (2006), Banik and Naskar (2006), Abbas (2005), Rawal and Tomar (1996) for Sahiwal, and Lathwal et al (1993) for Red Sindhi while higher estimates were observed by Upadhyay et al (2017) for Karan Fries; Goshu and Singh (2013) for HF cattle; Shahi and Kumar (2006) for J × SW cross and Atrey et al (2005) for Frieswal.…”
Section: Resultssupporting
confidence: 90%
“…Maximum mortality was observed mainly due to pneumonia and enteritis, which was in general agreement with findings of Singh and Gurnani (2004). This is probably because neonates are more susceptible to viral and bacterial infections.The present findings revealed that higher incidence of mortality was due to pneumonia and similar findings were also reported by Upadhyay (2013) and Reddy and Nagarcenkar (1989) for Sahiwal; and Maher et al (2015) for Tharparkar. Panmei et al (2016) reported that 3.…”
Section: Reasons Of Disposalsupporting
confidence: 91%
See 3 more Smart Citations